Analysis of Cyclamate Content in Packaged Beverages - Risqi Pricillia Nanda; Nur’ain Nur’ain; Ferdiansyah Ferdiansyah; Evril Yolanda; Suraya Suraya; Painingsih Painingsih; Zakiah Zakiah (PAKIS JOURNAL INSTITUTE, 2026)
Cyclamate is a type of synthetic sweetener that has a sweetness level approximately 30 times higher than sucrose. The purpose of this study was to determine the presence of cyclamate in beverages available on the market. This research employed a qualitative approach. The collected samples were subjected to a color reaction test to observe any chemical changes indicating the presence of cyclamate. A total of 12 beverage samples were obtained through random sampling.The results showed that 4 samples tested positive for cyclamate, specifically samples 1, 2, 3, and 4. Meanwhile, the remaining 8 samples (samples 5, 6, 7, 8, 9, 10, 11, and 12) showed negative results, as indicated by the absence of a characteristic reaction. In conclusion, further testing on sweetened beverages marketed to the public is necessary to ensure consumer safety and to minimize potential health risks, including cardiovascular diseases. Cyclamate is an artificial sweetener that should not be consumed excessively.